1969
DOI: 10.1111/j.1432-1033.1969.tb00794.x
|View full text |Cite
|
Sign up to set email alerts
|

L'acétylcholinestérase des organes électriques de Poissons (torpille et gymnote); complexes membranaires

Abstract: After extraction of the torpedo electric organ, three main molecular species, A, C, D, carrying the acetylcholinesterase activity have been found. This is observed in fresh-frozen organ extracts, toluene-autolysed organ extracts, or autolysis exsudate. A fourth species, B, appears during autolysis in the exsudate, or following treatment of the extracts by proteolytic enzymes, trypsin or a-chymotrypsin. A series of agents such as pH, p-hydroxymercuribenzoate, or pharmacological drugs, have been tried in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
52
1
4

Year Published

1970
1970
1996
1996

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(63 citation statements)
references
References 27 publications
6
52
1
4
Order By: Relevance
“…We have already proposed a model for the structure of the acetylcholinesterase multiple forms [5], which is consistent with the hydrodynamic data [4], the electron microscopic appearance of A, C, D, G and G' [5,6] and the conversion sequence that we obtained by proteolytic degradation or sonication of these enzymes [1,2,3,8]. The D molecule is the most complex and all others can be derived from it; it is made up of a compact assembly of three tetramers, attached to the tail.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…We have already proposed a model for the structure of the acetylcholinesterase multiple forms [5], which is consistent with the hydrodynamic data [4], the electron microscopic appearance of A, C, D, G and G' [5,6] and the conversion sequence that we obtained by proteolytic degradation or sonication of these enzymes [1,2,3,8]. The D molecule is the most complex and all others can be derived from it; it is made up of a compact assembly of three tetramers, attached to the tail.…”
supporting
confidence: 56%
“…In our previous studies we have shown that acetylcholinesterase from Electrophorus electricus electric organ exists in a number of distinct molecular forms [ 1,2], which differ markedly in their physical chemical characteristics. Three forms, D (18.4 S), C (14.2 S) and A (9 S), behave hydrodynamically as asymmetric particles [3,4] and are seen in the electron microscope to possess an elongated 'tail' [5,6], which the three other forms G (11.8 S), G' (7.7 S) and G" (5.3 S), are lacking.…”
mentioning
confidence: 99%
“…The early studies of Massoulie and Rieger [42] provided evidence that Torpedo electric organ also contains asymmetric forms of AChE which are similar to those observed in Electrophorus. Subsequent physicochemical studies revealed the presence of A12, A8 and A4 forms which were homologous to the corresponding forms in Electrophorus and could be similarly extracted at high ionic strength in the absence of detergent [32,51,52].…”
Section: Molecular Structurementioning
confidence: 91%
“…It was thus found that the aggregated fraction contained the asymmetric molecules A (9.2 S), C (14.2 S) and D (18.5 S), while the nonaggregated fraction contained only the globular form G (tetramer, 11.8 S) and G' (dimer 7.4 S). In an early publication [3] we had described the aggregation of the heavy D and C molecules, but since a slow-sedinienting peak remained unaggregated in low-ionicstrength conditions, we had assumed that the A form was not aggregating. However, the existence of dimers G', sedimenting in the same range, was not recognized at the time.…”
Section: Formation and Sedimentation Properties Of Acttylcholinestermentioning
confidence: 99%